2017
DOI: 10.1038/s41598-017-05089-3
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice breakup and marine melt of a retreating tidewater outlet glacier in northeast Greenland (81°N)

Abstract: Rising temperatures in the Arctic cause accelerated mass loss from the Greenland Ice Sheet and reduced sea ice cover. Tidewater outlet glaciers represent direct connections between glaciers and the ocean where melt rates at the ice-ocean interface are influenced by ocean temperature and circulation. However, few measurements exist near outlet glaciers from the northern coast towards the Arctic Ocean that has remained nearly permanently ice covered. Here we present hydrographic measurements along the terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…The PcW and ArAW layers were separated by warm halocline water at 70-100 m, while the cold and extraordinarily low salinity waters in the uppermost 15-20 m layer were diluted by local freshwater sources . Bendtsen et al (2017) reported on a similar vertical thermohaline structure west of FIIC glacier observed during the short ice-free period in August 2016. The only changes occurred in the surface layer, where considerable freshening (S < 10) and warming (θ > +2 • ) were observed in relation to snow/ice melting and solar radiative heating.…”
Section: Regional Oceanographic Settings Of the Southern Wandel Sea Smentioning
confidence: 57%
See 2 more Smart Citations
“…The PcW and ArAW layers were separated by warm halocline water at 70-100 m, while the cold and extraordinarily low salinity waters in the uppermost 15-20 m layer were diluted by local freshwater sources . Bendtsen et al (2017) reported on a similar vertical thermohaline structure west of FIIC glacier observed during the short ice-free period in August 2016. The only changes occurred in the surface layer, where considerable freshening (S < 10) and warming (θ > +2 • ) were observed in relation to snow/ice melting and solar radiative heating.…”
Section: Regional Oceanographic Settings Of the Southern Wandel Sea Smentioning
confidence: 57%
“…These data showed the absence of warm halocline water in the vicinity of the glacier, and Bendtsen et al (2017) argued that bottom water from the shelf can intrude below the tidewater glacier and cool to the freezing temperature through heat loss to the glacial ice. This cooling is not accompanied by basal melting, and hence the salinities of underlying water below the glacier are not changed.…”
Section: The Storm-induced Intrusions Of Cold Subglacial Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to a strong underlying density interface, this freshwater remains within the surface where it accumulates a large amount of solar radiation and becomes warmer. In August 2015, surface salinities within the ice‐free areas were below 10 while surface temperatures rose above 4°C at place and decreased toward 1.3°C at the MYI edge (Bendtsen et al, ). The warm freshwater layer predominantly occupied the uppermost 10 m of the water column (Bendtsen et al, ), and its persistence implies that the strong stratification suppressed vertical mixing.…”
Section: Discussionmentioning
confidence: 99%
“… SAR‐C satellite images showing the position of multiyear ice edge on (left) 17 August and (right) 19 August and positions of CTD casts carried out in 15–21 August 2015 (Bendtsen et al, ). The shape of symbols indicates the date of the CTD cast, and water temperature at 2 m depth is indicated by color shading.…”
Section: Discussionmentioning
confidence: 99%